Computation‐Guided Synthesis of New Garnet‐Type Solid‐State Electrolytes via an Ultrafast Sintering Technique. Issue 46 (13th October 2020) - Wang, Ruiliu; Ping, Weiwei; Wang, Chengwei; Liu, Yunsheng; Gao, Jinlong; Dong, Qi; Wang, Xizheng; Mo, Yifei; Hu, Liangbing
Abstract: The discovery of new solid‐state electrolytes (SSEs) can be guided by computation for next‐generation Li batteries toward higher energy density and better safety. However, conventional synthetic methods often suffer from severe loss of Li and poor material quality, therefore preventing the promise of the predicted SSE candidates to be realized. In this study, computationally predicted SSEs with desirable material quality are synthesized via an ultrafast sintering technique. Three new garnet‐type Li + conductors, including Li6.5 Nd3 Zr1.5 Ta0.5 O12 (LNZTO), Li6.5 Sm3 Zr1.5 Ta0.5 O12 (LSZTO), and Li6.5 (Sm0.5 La0.5 )3 Zr1.5 Ta0.5 O12 (L‐LSZTO), are screened by density functional theory to exhibit good synthesizability and stability. The ultrafast sintering method by Joule heating effectively shorten the sintering time from several hours to <25 s, thereby reducing the Li loss and effectively merging the grains toward high material quality. In agreement with the computational prediction, LNZTO demonstrates the best synthesizability and phase stability, thereby achieving the highest conductivity of 2.3 × 10 −4 S cm −1 among the three new SSE candidates. Using a current density of 0.2 mA cm −2, the Li/LNZTO/Li symmetric cell can cycle for ≈90 h without obvious increase of overpotentials. This study showcases the successful realization of computational predictions by the ultrafast sintering technique for the rapid optimization and screening of high‐performance SSEs. Abstract : New members of the family of garnet‐type solid‐state electrolytes (SSEs) including LNZTO, LSZTO, and L‐LSZTO are predicted by computation and synthesized by an ultrafast sintering technique. This study demonstrates the successful realization of computational predictions through the ultrafast sintering technique for the rapid optimization and screening of high‐performance SSEs.